1990
DOI: 10.2106/00004623-199072030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Cobb angle on radiographs of patients who have scoliosis. Evaluation of intrinsic error.

Abstract: To quantitate the intrinsic error in measurement, fifty anteroposterior radiographs of patients who had scoliosis were each measured on six separate occasions by four orthopaedic surgeons using the Cobb method. For the first two measurements (Set I), each observer selected the end-vertebrae of the curve; for the next two measurements (Set II), the end-vertebrae were pre-selected and constant. The last two measurements (Set Ill) were obtained in the same manner as Set II, except that each examiner used the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
297
5
20

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 533 publications
(347 citation statements)
references
References 5 publications
11
297
5
20
Order By: Relevance
“…These findings are in contrast to those reported by Shea et al [11], who found a statistically better correlation in digital, compared to manual measurement of curves. However the intra-and interobserver reliability results of this study are comparable with those from previous studies [2,6,8] (Table 4). Analysing these previous studies it can be shown that most authors choose scoliotic curves smaller than 40°which may not reflect the true every day clinical situation [4] ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in contrast to those reported by Shea et al [11], who found a statistically better correlation in digital, compared to manual measurement of curves. However the intra-and interobserver reliability results of this study are comparable with those from previous studies [2,6,8] (Table 4). Analysing these previous studies it can be shown that most authors choose scoliotic curves smaller than 40°which may not reflect the true every day clinical situation [4] ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…First, the mean angular difference was 2.81°±2.61°. The reproducibility of the Cobb angle measures obtained here appears equal to or better than previously reported for intra-observer or inter-observer studies using manual or computer-assisted techniques [4,5,15,17,18,20]. However, direct comparisons cannot be made with the previously mentioned studies because different radiographs were evaluated and differing statistical methods used in those studies.…”
Section: Discussionsupporting
confidence: 51%
“…Studies of inter-observer and intra-observer variability in measurement of this angle [3,7,9,15,16,20] have revealed that errors in radiographic measurements are typically ±5°and are comparable with thresholds of change that can influence treatment decisions [19]. Recent studies [4,5,8,14,18] demonstrate computer-assisted methods to reduce technical errors and the need for memorization of measurement and classification procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations